1989
DOI: 10.1038/ki.1989.227
|View full text |Cite
|
Sign up to set email alerts
|

Short and long term effects of antihypertensive therapy in the diabetic rat

Abstract: To compare the impact of differing antihypertensive regimens on the development of renal injury, studies were performed in three groups of moderately hyperglycemic diabetic rats, and one group of non-diabetic control (C) rats. One diabetic group (DM) received no therapy except insulin. The remaining diabetic groups received insulin and either the angiotensin I converting enzyme inhibitor captopril (CAP), or triple therapy (TRX) with reserpine, hydralazine and hydrochlorothiazide. CAP and TRX modestly and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
141
2
3

Year Published

1991
1991
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(159 citation statements)
references
References 44 publications
13
141
2
3
Order By: Relevance
“…Results with inhibitors of ACE have, however, suggested that glomerular hypertension rather than glomerular hyperfiltration in itself accounts for most of the increased proteinuria and the progress of nephropathy in such rats [9,25]. It has been shown that inhibition of ACE prevents the progress of diabetic glomerulopathy in normotensive diabetic rats when such inhibition causes PGC to become normal and remain there without change in the raised GFR [9].…”
Section: Discussionmentioning
confidence: 99%
“…Results with inhibitors of ACE have, however, suggested that glomerular hypertension rather than glomerular hyperfiltration in itself accounts for most of the increased proteinuria and the progress of nephropathy in such rats [9,25]. It has been shown that inhibition of ACE prevents the progress of diabetic glomerulopathy in normotensive diabetic rats when such inhibition causes PGC to become normal and remain there without change in the raised GFR [9].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment which successfully has reduced the progression in diabetic kidney disease both experimentally [8,9,25] and in clinical trials [12,13,16,17,26] has always been associated with a reduction in proteinuria during the intervention period. The association between albuminuria and progression of diabetic nephropathy, suggests that measurements of the initial antiproteinuric effect may provide a tool for rapid screening of the potential renoprotective effect of new drugs and non-pharmacological treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown the renoprotective effects of RAS inhibition in experimental diabetes [4], and these effects have been confirmed using both angiotensin converting enzyme inhibitors (ACEi) and angiotensin II receptor antagonists in models of hypertensive and normotensive diabetic nephropathy [5,6,7,8]. However, blockade of the RAS alone, both experimentally and clinically, only retards but does not prevent or reverse diabetic nephropathy [6,9]. Furthermore, it has been postulated that the effects of blockade of the RAS could be limited by the salt and water retention often found in experimental and clinical diabetes [10,11].…”
mentioning
confidence: 94%